Functional amino acid supplementation postweaning mitigates the response of normal birth weight more than for low birth weight pigs to a subsequent Salmonella challenge - L.A. Rodrigues; J.C. Panisson; L.A. Kpogo; J.C. González-Vega; J.K. Htoo; A.G. Van Kessel; D.A. Columbus (Animal, 2022)
Previous work has shown that dietary supplementation with key functional amino acids (FAA) improves growth performance and immune status of disease-challenged normal birth weight (NBW) pigs. It is not known whether FAA supplementation attenuates the effects of a subsequent disease challenge or whether this response is similar in low birth weight (LBW) pigs. The objective was to determine the effects of birth weight and FAA supplementation during the postweaning period in Salmonella-challenged pigs. Thirty-two LBW (1.08 ± 0.11 kg) and NBW (1.58 ± 0.11 kg) pigs were assigned to a nursery feeding program at weaning (25 d) for 31 days in a 2 × 2 factorial arrangement. Factors were birth weight category (LBW vs. NBW) and basal (FAA–) or supplemented FAA profile (FAA+; Thr, Met, and Trp at 120% of requirements). At d 31, pigs were placed onto a common grower diet and, after a 7-d adaptation period, were inoculated with Salmonella Typhimurium (ST; 2.2 × 109 colony-forming units/mL) and monitored for 7-d postinoculation. Growth performance, rectal temperature, fecal score, indicators of gut health, ST shedding score in feces, intestinal ST colonization and translocation, and blood parameters of acute-phase response and antioxidant balance were measured pre- and postinoculation. Inoculation with ST increased temperature and fecal score, and the overall rectal temperature was higher in LBW compared to NBW pigs (P < 0.05). Postinoculation (d 7), reduced:oxidized glutathione was increased in NBW compared to LBW pigs (P < 0.05). Salmonella shedding and translocation to spleen were lower in NBW-FAA+ compared to NBW-FAA− pigs (P < 0.05). Postinoculation average daily gain was higher in NBW-FAA+ (P < 0.05) compared to the other groups. Postinoculation haptoglobin, superoxide dismutase, and colonic myeloperoxidase were increased in LBW-FAA− pigs (P < 0.05). Ileal alkaline phosphatase was decreased in LBW compared to NBW (P < 0.05). Overall, FAA supplementation represents a potential strategy to mitigate the effect of enteric disease challenge in NBW, but not LBW pigs.